Three-dimensional water/fat separation and T 2 estimation based on whole-image optimization-Application in breathhold liver imaging at 1.5 T - Berglund, Johan; Kullberg, Joel (Magnetic resonance in medicine, 2012)
The chemical shift of water and fat resonances in proton MRI allows separation of water and fat signal from chemical shift encoded data. This work describes an automatic method that produces separate water and fat images as well as quantitative maps of fat signal fraction and T 2* from complex multiecho gradient‐recalled datasets. Accurate water and fat separation is challenging due to signal ambiguity at the voxel level. Whole‐image optimization can resolve this ambiguity, but might be computationally demanding, especially for three‐dimensional data. In this work, periodicity of the model fit residual as a function of the off‐resonance was used to modify a previously proposed formulation of the problem. This gives a smaller solution space and allows rapid optimization. Feasibility and accurate separation of water and fat signal were demonstrated in breathhold three‐dimensional liver imaging of 10 volunteer subjects, with both acquisition and reconstruction times below 20 s. Magn Reson Med, 2011. © 2011 Wiley Periodicals, Inc.